Arsenic Transport and Adsorption Modeling in Columns Using a Copper Nanoparticles Composite - Alvarez-Gutierrez, P; Contreras-Bravo, S; Henriquez-Vargas, L (Elsevier Ltd, 2017)
Adsorption effectivity of a new composite with copper nanoparticles on polyamide support, PA-NCu in fixed bed columns was assessed to treat a continuous flow of water with arsenic, having previously determined the equilibrium parameters at a batch level. The experimental results allowed to calibrate and validate a transport model, which includes a retardation factor based on a Langmuir equilibrium and an additional As decay reaction. The retardation factor is dependent of the adsorption capacity of the PA-NCu and the As concentration, with greater incidence at the process beginning where the adsorption predominated and until breakthrough time, tending to decrease towards adsorbent saturation. The retardation increased significantly with the real adsorption capacity and less so with the decrease of the initial As concentration, which improved the composite s adsorption capacity when compared to a retardation based on a linear equilibrium. The decay reaction s effect is minimum during the initial stage but influences the saturation levels achieved. The model allowed to predict the effect of the adsorption capacity in columns as a function of the composite s characteristics and the initial As concentration, which allows us to infer that improving the support type and increasing the nanoparticles availability will advance towards its use in field applications. © 2017 Elsevier Ltd